Analysis of Macroeconomic Variables and Fundamental Analysis of Indonesia Shariah Stock Index (ISSI) - Amru Sukmajati; Dyah Ayu Fitri Hastuti (International Journal of Seocology, 2019)
This study atempts to analyze the effect of domestic macroeconomic variables: Inflation and BI Rate; global macroeconomic variables: World Oil Price (WTI); and financial ratios by using fundamental analysis: Earning Per Share (EPS), Price to Earning Ratio (PER), Debt to Equity Ratio (DER), dan Return On Equity (ROE) against Indonesia Sharia Stock Index (ISSI). This study uses quantitative method with multiple linier regression analysis with quarterly time sequences from the 1st quarter of 2011 to the 4th quarter of 2016. The data obtained from Dunia Investasi, Bank Indonesia’s Report, Economagic, and Indonesia Stock Exchange. The sample was taken using purposive sampling and data was collected by recording techniques. The result of this study shows that all variables are influential where ISSI is negatively affected by World Oil Price (WTI), and positively affected by Inflation, BI Rate, EPS, PER, DER, and ROE.